2021
DOI: 10.1155/2021/8894160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Articaine and Lidocaine Anesthetics on Blood Pressure after Maxillary Infiltration Technique: A Triple-Blind Randomized Clinical Trial

Abstract: Background. Many dental procedures begin with local anesthesia. Subsequent increase in blood pressure in healthy individuals commonly occurs and may be affected by several factors such as mental and physical stress, painful stimuli, and action of catecholamines present in local anesthetic solutions. The aim of the present study is to compare the effects of 4% articaine with 1 : 100000 epinephrine and 2% lidocaine with 1 : 80000 epinephrine on blood pressure after maxillary infiltration technique. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The results of this study also showed that none of the vital signs showed significant differences in the two groups of conventional and two-step injection techniques. Moaddabi et al [39] showed that blood pressure increased after lidocaine injection; the results of this study demonstrated that this injection did not cause significant differences in participants' vital signs. However, because no study has examined the vital signs before and after injection of conventional and two-step injection techniques, it is not possible to compare this finding with other studies.…”
Section: Discussionsupporting
confidence: 48%
“…The results of this study also showed that none of the vital signs showed significant differences in the two groups of conventional and two-step injection techniques. Moaddabi et al [39] showed that blood pressure increased after lidocaine injection; the results of this study demonstrated that this injection did not cause significant differences in participants' vital signs. However, because no study has examined the vital signs before and after injection of conventional and two-step injection techniques, it is not possible to compare this finding with other studies.…”
Section: Discussionsupporting
confidence: 48%
“…Overall, an effect of articaine on the T -wave can be excluded in the present study. Injection stress: The mental stress due to the upcoming injection means an activation of the sympathetic nervous system [ 28 ]. The T -wave amplitude ( T AM ) as a psychophysiological index for the sympathetic drive has been sustainably reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…however, there was no significant difference between the two drugs in increasing blood pressure. [51] Studies have shown that articaine is safe and reliable and can be used as a substitute for lidocaine in local infiltration anesthesia. Articaine has the shortest metabolic half-life, and high-dose injections can be used to significantly reduce post-implantation reactions.…”
Section: Introductionmentioning
confidence: 99%